Nitrous oxide emissions from wetland soil amended with two types of cattle manure - Johnson Masaka; Justice Nyamangara; Menas Wuta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The implications of increased applications of high quality cattle manure to agricultural systems in Africa on N2O emissions are still only partially understood. Methods A field experiment was carried out in a wetland in central Zimbabwe to determine the effects of cattle manure quality on emissions of N2O during the growing seasons of rape and tomato crops. The static chamber and gas chromatography techniques were used to capture and measure fluxes of N2O. Results The substitution of low N by high N manure significantly increased N2O fluxes and total N lost through N2O emission. Emissions of N2O increase with increasing content of N in applied manure. Conclusions Given that N2O in agricultural soil is produced predominantly through the microbial transformations of inorganic N, the potential of a soil to emit N2O increases with the increasing availability of N and consequently the N content in applied manure. The applications of lower rate of high and low N manures were followed by lower emissions of N2O, a result that is favorable to the objective of lowering the contribution of agricultural sources to the global greenhouse gas emissions. The loss of N in emissions of N2O expressed per unit mass of harvested dry matter yield decreases with increasing manure application, dry matter yield and N uptake. Improved agronomic practices for increased crop productivity can be used as a mitigation factor for reducing the contribution of agriculture in the global emissions of N2O.